Management of Dry Socket: A Systemic Review - Dixit, Charu; Singh, Prakash (Journal of Orofacial Research, 2017)
Dry socket or alveolar osteitis or sicca Dolorosa is commonly associated complication following extraction of third molars. Hindrance of the clot within the extraction socket which disrupts healing process is the basic phenomena happened in dry socket. The correct etiology of sicca Dolorosa remains unclear but it allied with severe postoperative pain and discomfort to the patient. Therefore we aim to review this article which gives a brief overview of the clinical features, etiology and the management of dry socket.